Work in a Home Office System – Opinions of a Group of Managers in an MBA Program - Moczydłowska, Joanna M. (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2021)
Objective: Examining managers’ attitudes towards remote work. Research Design & Methods: Literature analysis, FGI. Findings: Managers are aware of the benefits and risks of working in a home office model. They emphasise the difficult situation of parents whose children are being educated online and employees with low skills in using new technologies. The benefits of working remotely are significant and clearly outweigh the potential risks. Implications / Recommendations: Managers are aware of the benefits and risks of working in a home office model. After the COVID-19 pandemic ends, remote work will be used on a much larger scale than it was before the pandemic. In e-work conditions, managerial competences become more important: communication skills, building relationships based on trust, and the ability to plan and organise work. Contribution: Deepening and actualising knowledge of home office work through an examination of managers’ attitudes towards this form of work.